Improving ISSSTE's Public Procurement for Better Results (OECD Public Governance Reviews, 2016)
OECD countries are increasingly attempting to achieve savings through their public procurement systems, in particular in healthcare. In 2012, the State’s Employees’ Social Security and Social Services Institute in Mexico (ISSSTE) asked the OECD to review the effectiveness and integrity of its procurement system and to address bid-rigging. Many of the OECD’s recommendations led to enduring reforms at ISSSTE. In 2015 the OECD conducted a new review focusing on planning and coordination of procurement activities, market research and improvement of medical services. This report presents the findings of the review and notes the ISSSTE’s recent achievements. It also makes recommendations to support the alignment of the ISSSTE’s procurement practices with the 2015 OECD Recommendation of the Council on Public Procurement and includes action plans for priority activities